Evaluation of upper extremity movements in patients with breast conserving treatment with the disabilities of the arm, shoulder and hand (DASH) questionnaire (Annals of Medical Research, 2023)
Aim: Surgery and radiotherapy (RT) are local treatment methods that constitute organ-preserving treatment in breast cancer. Limitations of arm movements and lymphedema are known side effects that may adversely affect quality of life. With the DASH questionnaire, the extent of the limitation and complaints by answering the questions evaluating the weakness in arm movements were used to understand the patients condition. DASH basically consists of a 30-item scale and is scored from 0 to 100. The DASH questionnaire was applied to patients who underwent breast-conserving surgery to evaluate their upper extremity functions.Materials and Methods: 18 patients with breast cancer who underwent breast conserving surgery (BCS) and RT treatments were evaluated with at least 6 months follow-up. The DASH questionnaire was applied to the patients who are included. The test consists of two parts and the first part used on function evaluation and symptoms includes 30 questions.Results: The median age of the patients was 45 (range: 31-67). Sentinel lymph node dissection (SLND) with BCS is the surgical method performed in all patients, but axillary lymph node dissection (ALND) was added to 13 patients with sentinel node positivity during surgery. All patients received RT. The DASH questionnaire was performed at a median postoperative 14 month (range: 6-25 months). As a result of DASH, the mean scores of the patients were found to be 23.2 (range: 1.7-59.2). Distant metastasis was detected in one of the patients, and no recurrence or metastasis was found in the other patients.Conclusion: DASH questionnaire study was concluded as limited arm movements at the patients despite the advanced surgical and RT techniques. In terms of quality of life, recommendations are important and patients could be informed about arm movements starting from the preoperative period.